2019
DOI: 10.1039/c8ra09398a
|View full text |Cite
|
Sign up to set email alerts
|

The phase diagram of a mixed halide (Br, I) hybrid perovskite obtained by synchrotron X-ray diffraction

Abstract: The phase diagram elucidates structural changes and phase separation effects, induced by halide substitution in hybrid perovskite MAPb(I,Br)3 solid solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
104
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 40 publications
12
104
1
Order By: Relevance
“…[ 48 ] With the assumption that lattice dilation is the dominant factor for the temperature‐dependent shift of the PL maximum, [ 6,12 ] we find tensile strain values of 85–165 MPa (see Section S7 in the Supporting Information for details). However, recent studies demonstrated that the unit cell volume of the orthorhombic phase is smaller than the one of the tetragonal phase, [ 4,45,49,50 ] and thus there should be compressive strain instead of tensile strain to affect the tetragonal inclusions. Room temperature measurements showed that pressure on MAPbI 3 leads to a red shift.…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] With the assumption that lattice dilation is the dominant factor for the temperature‐dependent shift of the PL maximum, [ 6,12 ] we find tensile strain values of 85–165 MPa (see Section S7 in the Supporting Information for details). However, recent studies demonstrated that the unit cell volume of the orthorhombic phase is smaller than the one of the tetragonal phase, [ 4,45,49,50 ] and thus there should be compressive strain instead of tensile strain to affect the tetragonal inclusions. Room temperature measurements showed that pressure on MAPbI 3 leads to a red shift.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent are structural dependencies on halide and A + composition. MAPbI 3 ( Figure IA) adopts a β-phase at 300 K and transitions to its α-phase at~330 K. MAPbBr 3 prefers its α-phase above~250 K ( Figure IB) [74]. FAPbI 3 ( Figure IC) assumes its α-phase above~440 K but prefers its non-perovskite δ hex -phase at~300 K [13].…”
mentioning
confidence: 99%
“…The upper bound of the temperature window for the tetragonal phase is only 20 K before the lattice becomes cubic, and such an interval is too narrow to extract accurate fitting parameters considering that intermediate phases might exist. 54 However, for the sake of completeness, we added the expected transition point from literature data at 403 K. 20 …”
mentioning
confidence: 99%